- 29

- 0

Prove (given that A+B+C=π):

[tex]\sin^2 A + \sin^2 B - \sin^2 C = 2 \sin A \sin B \sin C[/tex]

I got this far:

[tex]\begin{matrix}\mbox{LHS} & = & \sin^2 A + \sin^2 B - \sin^2 C \\ \ & = & \sin^2 A + \left ( \sin B + \sin C \right ) \left ( \sin B - \sin C \right ) \\ \ & = & \sin^2 A + \left ( 2 \sin \frac{B+C}{2} \cos \frac{B-C}{2} \right) \left ( 2 \cos \frac{B+C}{2} \sin \frac{B-C}{2} \right ) \\ \ & = & \sin^2 A + \left (2 \sin \frac{A}{2} \cos \frac{B-C}{2} \right) \left ( 2 \cos \frac{-A}{2} \sin \frac{B-C}{2} \right ) \\ \ & = & \sin^2 A + \left ( -2 \sin \frac{A}{2} \cos \frac{A}{2} \right ) \left ( 2 \cos \frac{B-C}{2} \sin \frac{B-C}{2} \right ) \\ \ & = & \sin^2 A + \left ( -2 \sin A \right ) \left (2 \cos \frac{B-C}{2} \sin \frac{B-C}{2} \right ) \end{matrix}[/tex]

Help please...

TIA

[tex]\sin^2 A + \sin^2 B - \sin^2 C = 2 \sin A \sin B \sin C[/tex]

I got this far:

[tex]\begin{matrix}\mbox{LHS} & = & \sin^2 A + \sin^2 B - \sin^2 C \\ \ & = & \sin^2 A + \left ( \sin B + \sin C \right ) \left ( \sin B - \sin C \right ) \\ \ & = & \sin^2 A + \left ( 2 \sin \frac{B+C}{2} \cos \frac{B-C}{2} \right) \left ( 2 \cos \frac{B+C}{2} \sin \frac{B-C}{2} \right ) \\ \ & = & \sin^2 A + \left (2 \sin \frac{A}{2} \cos \frac{B-C}{2} \right) \left ( 2 \cos \frac{-A}{2} \sin \frac{B-C}{2} \right ) \\ \ & = & \sin^2 A + \left ( -2 \sin \frac{A}{2} \cos \frac{A}{2} \right ) \left ( 2 \cos \frac{B-C}{2} \sin \frac{B-C}{2} \right ) \\ \ & = & \sin^2 A + \left ( -2 \sin A \right ) \left (2 \cos \frac{B-C}{2} \sin \frac{B-C}{2} \right ) \end{matrix}[/tex]

Help please...

TIA

Last edited: